2016
DOI: 10.1021/jacs.6b03963
|View full text |Cite
|
Sign up to set email alerts
|

Development of Enantiospecific Coupling of Secondary and Tertiary Boronic Esters with Aromatic Compounds

Abstract: The stereospecific cross-coupling of secondary boronic esters with sp2 electrophiles (Suzuki–Miyaura reaction) is a long-standing problem in synthesis, but progress has been achieved in specific cases using palladium catalysis. However, related couplings with tertiary boronic esters are not currently achievable. To address this general problem, we have focused on an alternative method exploiting the reactivity of a boronate complex formed between an aryl lithium and a boronic ester. We reasoned that subsequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
103
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 140 publications
(103 citation statements)
references
References 73 publications
0
103
0
Order By: Relevance
“…At this point, we decided to optimize the reaction conditions to maximize the formation of either 4 a or 4 b , initially focusing on the maximally functionalized boron‐incorporated product 4 b . We had previously observed such products when coupling electron‐rich aromatics with boronic esters and found that i PrOH/MeCN gave the best ratio 3b. We therefore carried out a brief solvent study (entries 2–5) and again found that i PrOH/MeCN was optimal here too, giving the highest ratio, leading to a 76 % yield of 4 b (entry 4).…”
mentioning
confidence: 87%
“…At this point, we decided to optimize the reaction conditions to maximize the formation of either 4 a or 4 b , initially focusing on the maximally functionalized boron‐incorporated product 4 b . We had previously observed such products when coupling electron‐rich aromatics with boronic esters and found that i PrOH/MeCN gave the best ratio 3b. We therefore carried out a brief solvent study (entries 2–5) and again found that i PrOH/MeCN was optimal here too, giving the highest ratio, leading to a 76 % yield of 4 b (entry 4).…”
mentioning
confidence: 87%
“…The reaction involves initial formation of aryl boronate I through Li–B exchange of an aryl lithium and an alkylboronic ester 6. Subsequent addition of an electrophilic halogenating agent (NBS= N ‐bromosuccinimide) to I forms oxocarbenium II (structure drawn for clarity although a concerted mechanism has been proposed),3b which promotes a 1,2‐metallate rearrangement giving the neutral boronic ester III . Finally, rearomatization‐driven elimination of the halide and the boronic ester group generates the substituted aryl product.…”
mentioning
confidence: 99%
“…Species VII undergoes a 1,2‐metallate rearrangement to give boronic ester VIII . It is likely that oxidation of intermediate VI leads directly to boronic ester VIII but species VII is drawn for clarification 3b. Under oxidative conditions (K 2 CO 3 , I 2 ), rearomatization occurs to form the final three‐component‐coupled products with complete enantiospecificity.…”
mentioning
confidence: 99%
“…furan, thiophene, indole, and benzofuran) and electron‐rich aromatics, provided they were substituted with donor groups at the meta ‐position. The meta donor group and the electron‐rich boronate worked synergistically to promote an electrophilic reaction on the aromatic ring 5a,5b. Positioning the donor group in the para ‐position pushes electron density onto the sp 3 carbon atom of the boronate complex, resulting in a selective reaction via an S E 2 pathway, rather than an S E Ar pathway (e.g.…”
mentioning
confidence: 99%
“…Positioning the donor group in the para ‐position pushes electron density onto the sp 3 carbon atom of the boronate complex, resulting in a selective reaction via an S E 2 pathway, rather than an S E Ar pathway (e.g. Scheme 1 c, left‐hand side) 5b, 7…”
mentioning
confidence: 99%